PENGARUH PERILAKU KEPEMIMPINAN KEPALA SEKOLAH MOTIVASI KERJA GURU DAN KOMITMEN KERJA GURU TERHADAP KINERJA SEKOLAH SMP NEGERI DI KECAMATAN KUTOWINANGUN KABUPATEN KEBUMEN TAHUN PELAJARAN 2012/2013 (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
This study aims to reveal: the influence of principal’s leadhership behaviors, the motivation, and the teacher’s work commitment on the school performance of Public Junior High School in the Kutowinangun Sub District Kebumen Regency 2012/2013.This is an expost facto research. The population of the research is all teachers of Public Junior High School of Kutowinangun Sub Distric Kebumen Regency 2012/2013.The sample contains of 95 teachers which is determined by random sampling technique based on the determination of the amount of sample table developed by Isaac and Michael. The instruments for the data collection were questionnaires using a Likert scale respectively had been tested againts the validity and reliability by using the analysis Alpha Cronbach formula.The data analysis technique used were descriptive and inferential analyzes, multiple regresssion and partial correlation. Descriptive analysis results indicate that the performance of school in the Public Junior High School of Kutowinangun Sub District, Kebumen Regency school year 2012/2013 is 43.16% is high There is a positive influence of Principal’s Leadership Behaviors on School Performance, there is a positive influence of Work Motivation Teacher on school performenc, there is no influence of Commitmenton the Performance of the School, and simultaneously influence on the school performance with multiple correlation coefficient an R value for 0,686 indicating that the simultaneous Principal’s Leadership Behaviors, Work Motivation and Work Commitment Teacher’s Performance influence on School Performance of Secondary Schools in Kutowinangun Sub District, Kebumen Regency school year 2012/2013 amounted to 68,6% and the remaining 31,4% is influenced by other factors not examined in thisstudy.